2019
DOI: 10.1002/cncy.22164
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma‐associated protein 1 is a robust nuclear immunostain for the diagnosis of small cell lung carcinoma in cytology smears

Abstract: Background In a significant percentage of patients with small cell lung carcinoma (SCLC), cytology samples represent the only source of tumor tissue. Ancillary immunocytochemistry (ICC) for neuroendocrine markers is an important adjunct for the diagnosis of SCLC. Insulinoma‐associated protein 1 (INSM1) is a novel neuroendocrine marker proposed as an economical single‐marker alternative to the traditional 3‐marker panel of chromogranin, synaptophysin, and CD56. To the authors’ knowledge, limited studies have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In another study that also used cell block tissues, INSM1 was positive in 97% of 32 SCLC cases with a diffuse and strong staining pattern 18 . A recent study evaluating INSM1 staining in 70 SCLC cases, 33 of which were stained on smears, reported that INSM1 staining was positive in 91% of cases 19 . In that study, 11 tumors had direct smears matched with small biopsy specimens, and only 1 of the tumors showed false‐negative INSM1 staining on a direct smear.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study that also used cell block tissues, INSM1 was positive in 97% of 32 SCLC cases with a diffuse and strong staining pattern 18 . A recent study evaluating INSM1 staining in 70 SCLC cases, 33 of which were stained on smears, reported that INSM1 staining was positive in 91% of cases 19 . In that study, 11 tumors had direct smears matched with small biopsy specimens, and only 1 of the tumors showed false‐negative INSM1 staining on a direct smear.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, because the study consisted of cases with a known diagnosis of NET from various primary organ systems, the specificity of each marker could not be determined. Upon a careful review of the literature, we found that the reported specificity of INSM1 in a number of studies, including 2 cytology studies, was >95% 5‐9,12,14,17,19 . Notably, INSM1 can occasionally be reactive (usually weakly and focally) in non‐NETs, including squamous cell carcinomas and various salivary gland carcinomas of the head and neck 7 ; lung adenocarcinomas and squamous cell carcinomas 6,9 ; and adrenal cortical carcinomas, solid pseudopapillary neoplasms, cholangiocarcinomas, and adenocarcinomas of the colon, breast, and prostate 13,25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is little research on whether they are useful markers for the early detection of OSCC. Combining cytology and ICC to increase diagnostic accuracy has also been widely researched in other locations, but few studies have been conducted in the oral cavity [34,[44][45][46][47][48][49]. Our study thus offers a new cytological diagnosis tool for OSCC.…”
Section: Discussionmentioning
confidence: 89%
“…38 Recent studies demonstrated the diagnostic utility of INSM1 in other organs when the obtained tissue was scant in either a small biopsy or a cell block of cytology specimens as an alternative or effective stand-alone neuroendocrine marker. 13,15,33,39-43 Taken together, INSM1, especially when combined with either CT or mCEA, may potentially replace a panel of the traditional MTC markers or be the first line of choice among the MTC immunohistochemical markers when the obtained lesional tissue is quantitatively limited.…”
Section: Discussionmentioning
confidence: 99%